Reconsidering empirical cotrimoxazole prophylaxis for infants exposed to HIV infection - Gill Christopher J.; Sabin Lora L.; Tham Joseph; Hamer Davidson H. (The World Health Organization, 2004)
Infants with HIV infection are vulnerable to Pneumocystis carinii pneumonia (PCP) during their first year of life. WHO and the Joint United Nations Programme on HIV/AIDS now recommend that all children of HIV-positive mothers receive prophylactic cotrimoxazole against PCP from six weeks of age and continue this therapy until exposure through breast milk ceases and the infant is confirmed to be HIV-negative (rarely before one year of age). Empirical prophylaxis invokes a trade-off between possible benefit to the infant versus the risk of resistance to antibiotics and antimalarials. From a critical analysis of the literature, we offer a conceptual model demonstrating how, under certain circumstances, a policy of mass cotrimoxazole prophylaxis may be counterproductive.